Pełzanie Półpłaszczyzny przy Mieszanych Warunkach Brzegowych - Piekarski, Z.; Szefer, G. (Engineering Transactions, 1970)
Considered here is the problem of a half-plane made of visco-elastic material subjected to the Arutunian theory of ageing, at mixed boundary conditions corresponding to Griffith’s crack. By means of the Fourier integral transformation and elements of the theory of distribution, the problem has been reduced to a set of integral equations for which the exact closed solution is given. In particular, the displacements are determined in a portion of the slit, yielding an interesting result that expresses the creeping of this part of the boundary as the product of elastic displacement and the creep function.